2002
DOI: 10.1111/1468-2419.00157
|View full text |Cite
|
Sign up to set email alerts
|

Minimum and preferred entry qualifications and training provision for British workers

Abstract: This article reports the outcomes of a survey of British employers that requested information on the qualifications sought when recruiting employees, and on training and development offered subsequently to employees. Responses revealed that few employers actively sought vocational awards in potential employees. The only occupational category for which more employers specified a vocational award than an academic award was service workers. A substantial number of organisations specified no minimum entry level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…A study by Miller, Acutt, and Kellie (2002) questions the proposition that employers are either recruiting workers with qualifications or they are training them within the firm. Their survey of UK employers found that for most occupational groups those who recruited without qualifications were also less likely to subsequently train.…”
Section: Recruiting Qualifications?mentioning
confidence: 99%
“…A study by Miller, Acutt, and Kellie (2002) questions the proposition that employers are either recruiting workers with qualifications or they are training them within the firm. Their survey of UK employers found that for most occupational groups those who recruited without qualifications were also less likely to subsequently train.…”
Section: Recruiting Qualifications?mentioning
confidence: 99%
“…In some communities, a significant proportion of the employment opportunities available may be low paid, casualised and insecure, locking families into a low pay/no pay cycle and recurrent poverty (see McQuaid, Fuertes, & Richard, 2010;Metcalf & Dhudwar, 2010: Ray, Hoggart, Vegeris, &Taylor, 2010Shildrick, MacDonald, Webster, & Garthwaite, 2010;Tomlinson & Walker, 2010). Entry into these jobs is often via recruitment and selection processes that afford limited importance to qualifications (see Atkinson & Williams, 2003;Bates, Gifford & Johnson, 2008;Bryson, James, & Keep, 2012;Bunt, McAndrews, & Kuechel, 2005;Jackson et al, 2002;Miller, Acutt, & Kelly, 2002;Newton, Hurstfield, Miller, Page, & Akroyd 2005;Shury, Davies, Riley, & Stansfield, 2008;Spilsbury & Lane, 2000;UKCES, 2012). Moreover, the emphasis some employers place on recruiting on the basis of soft skills may work to the disadvantage of those from lower socio-economic backgrounds, as the soft skills being sought are often a proxy for class attributes (Payne, 2000;Warhurst & Nickson, 2001).…”
Section: Reality Fights Backmentioning
confidence: 99%
“…This tends to be caused by two reasons: many of the social and generic 'skills' required by employers are uncertified; and the formal skill levels needed in many lower-end jobs are often limited (see Miller, Acutt, and Kellie 2001;Newton et al 2005;Bates, Gifford, and Johnson 2008;Shury et al 2008). The widespread use of informal methods of recruitment and selection, such as word of mouth recommendation or work trials, further serves to weaken the role and impact of qualifications (Keep and James 2010a).…”
Section: Recruitment Selection and The Wage Effects Of Vqsmentioning
confidence: 99%